Surgical algorithm for sentinel lymph nodes detection in early-stage cervical cancer. (1st November 2019) - Balaya, V; Guani, B; Magaud, L; Bonsang-Kitzis, H; Deloménie, M; Nguyen-Xuan, H-T; Koual, M; Montero macias, R; Bresset, A; Ngo, C; Bats, A-S; Mathevet, P; et al.
Abstract : Introduction/Background: The aim of this study was to describe and assess a surgical algorithm for sentinel lymph nodes (SLN) detection in early-stage cervical cancer to improve lymph node staging. Methodology: Two French prospective multicentric database on SLN biopsy for cervical cancer (SENTICOL I and II) were analyzed. SLN detection was performed with a combined labeling technique (Patent blue and radioactive tracer). Patients who underwent both SLN biopsy and pelvic lymphadenectomy (PLND) were included. SLN and non-SLN were recorded according to the Marnitz classification. The surgical algorithm was retrospectively applied and consisted in exploration the following area: external iliac and interiliac, the common iliac, parametrial and presacral and paraaortic area. In case of no SLN detected in a hemi-pelvis, a full PLND was performed. Results: Between January 2005 and July 2012, 305 patients from 23 centers fulfilled the inclusion criteria. Median SLN detected was 3 and median total LN harvested was 17. At least one SLN was found in 92.8% of patients while bilateral detection rate was 74.6%. At final pathologic examination, 61 patients (20%) had LN metastases. Among the cases that at least one SLN detected, SLN diagnosed 52 of 57 patients with LN involvement (Sensitivity = 91.2% and Negative predictive value = 97.8%). By applying the algorithm, all patients with LN metastasis were identified. In case of bilateral SLN detection, no false negative was found and bilateral negative SLN predicted accurately the absence of LN metastases. In these cases, 79.8% of PLND would be avoided. Conclusion: This multicentric evaluation validates the use of a surgical SLN algorithm in early-stage cervical cancer. Full lymphadenectomy could be omitted in case of bilateral negative SLN. This algorithm permits to identify all patients with nodal spread and may imply a decrease of unjustified PLND. Disclosure: Nothing to disclose.